High-level inhibition of mitochondrial complexes III and IV is required to increase glutamate release from the nerve terminal - GLUCHOWSKA, SONIA AGNIESZKA; DAVEY, GAVIN (My University, 2011)
Background: The activities of mitochondrial complex III (ubiquinol-cytochrome c reductase, EC 1.10.2.2) and complex IV (cytochrome c oxidase EC 1.9.3.1) are reduced by 30-70% in Huntington's disease and Alzheimer's disease, respectively, and are associated with excitotoxic cell death in these disorders. In this study, we investigated the control that complexes III and complex IV exert on glutamate release from the isolated nerve terminal. Results: Inhibition of complex III activity by 60-90% was necessary for a major increase in the rate of Ca2+-independent glutamate release to occur from isolated nerve terminals (synaptosomes) depolarized with 4-aminopyridine or KCl. Similarly, an 85-90% inhibition of complex IV activity was required before a major increase in the rate of Ca2+-independent glutamate release from depolarized synaptosomes was observed. Inhibition of complex III and IV activities by ~ 60% and above was required before rates of glutamate efflux from polarized synaptosomes were increased. Conclusions: These results suggest that nerve terminal mitochondria possess high reserves of complex III and IV activity and that high inhibition thresholds must be reached before excess glutamate is released from the nerve terminal. The implications of the results in the context of the relationship between electron transport chain enzyme deficiencies and excitotoxicity in neurodegenerative disorders are discussed.
PUBLISHED
Keywords: Neuroscience; Biochemistry; HUNTINGTONS-DISEASE; PARKINSONS-DISEASE; ALZHEIMERS-DISEASE; Neuroscience